Taxonomic reassessment of the Little pocket mouse, Perognathus longimembris (Rodentia, Heteromyidae) of southern California and northern Baja California - Patton, James L.; Fisher, Robert N. (THERYA, 2023)
The Little pocket mouse (Perognathus longimembris) encompasses 15 to 16 currently recognized subspecies, six of which are restricted to southern California and adjacent northern Baja California. Using cranial geomorphometric shape parameters and dorsal color variables we delineate six regional groups of populations from this area that we recognize as valid, but these differ in name combination and geographic range from the current taxonomy. We resurrect two names from their current placement in synonymies, synonymize two currently recognized subspecies, and we reassign a third. Importantly, we restrict the U. S. Federally endangered Pacific pocket mouse (P. l. pacificus Mearns) to the vicinity of its type locality at the mouth of the Tijuana River in the southwestern corner of San Diego County and resurrect P. l. cantwelli von Bloeker for the other two population segments along the coast, those that span the northwestern corner of San Diego County and adjacent Orange County and that in coastal Los Angeles County. The name cantwelli would now apply to the only extant populations of the Pacific pocket mouse, a reassignment with obvious management implications. Our taxonomic decisions also reconfigure the ranges of other subspecies of conservation concern, notably P. l. bangsi Mearns and P. l. brevinasus Osgood.